An approach to application for LiNi0.6Co0.2Mn0.2O2 cathode material at high cutoff voltage by TiO2 coating - Chen, Yanping; Zhang, Yun; Chen, Baojun; Wang, Zongyi; Lu, Chao (Journal of power sources, 2014)
Nickel-rich LiNi0.6Co0.2Mn0.2O2 cathode material is coated with nano-sized anatase TiO2 synthesized via hydrolyzation method to improve its electrochemical performance at high cutoff voltage of 4.5 V. Scanning electron microscopy (SEM), transmission electron microscope (TEM) and high resolution transmission electron microscope (HRTEM) results show that the anatase TiO2 is successfully coated on the surface of LiNi0.6Co0.2Mn0.2O2 with nanoscale and the coating layer thickness is about 25–35 nm. X-ray diffraction (XRD) test results indicate that appropriate amount of TiO2 coating is beneficial to form a good layered structure with less cation disorder. Charge–discharge test results demonstrate that the TiO2-coated LiNi0.6Co0.2Mn0.2O2 presents excellent cycling capability, rate capability and thermal stability at cutoff voltage of 4.5 V. The 1.0 wt.% TiO2-coated LiNi0.6Co0.2Mn0.2O2 exhibits a capacity retention of 88.7% after 50 cycles at 1 C and a discharge capacity of 135.8 mAh g−1 after 10 cycles at 5 C, comparing to those of the pristine LiNi0.6Co0.2Mn0.2O2 of only 78.1% and 85.4 mAh g−1. Electrochemical impedance spectroscopy (EIS) and differential scanning calorimeter (DSC) tests results provide evidence that the improved electrochemical properties are mainly attributed to the suppression of the interface reaction between the cathode and electrolyte and the improvement of structural stability of the material by coating. •Anatase nano-TiO2 is successfully coated on the surface of LiNi0.6Co0.2Mn0.2O2.•Appropriate amount of TiO2 is beneficial to reduce cation disorder.•The 1.0 wt.% TiO2-coated LiNi0.6Co0.2Mn0.2O2 exhibits excellent electrochemistry properties.•The TiO2-coated LiNi0.6Co0.2Mn0.2O2 presents excellent thermal stability.